Consumer Well-Being: Effects of Subgoal Failures and Goal Importance - Devezer, Berna; Sprott, David E.; Spangenberg, Eric R.; Czellar, Sandor (Journal of Marketing, 2014)
Although there is increased awareness of issues surrounding consumer well-being, consumers often lack the personal commitment to improve their quality of life. This article builds on the concept of a goal hierarchy to propose that small acts may have unintended, large consequences on various domains of consumer well-being. A decrease in commitment to well-being goals (e.g., sustaining the natural environment) may stem from people's failure to achieve everyday subgoals (e.g., failing to recycle a newspaper). Four experiments in three contexts (i.e., consumer overspending, environmentally friendly behaviors, and charitable donations) show that when people perceive the endgoal as unimportant, even a single behavioral failure may reduce commitment to a well-being endgoal and weaken future intentions to perform behaviors that improve their quality of life. In addition, goal importance moderates the adverse relationship between subgoal performance and endgoal commitment. The authors present consumer-specific and marketer-controlled drivers of goal importance (i.e., goal visualization, self-relevance of goals, and aversive consequences of subgoal failure) and discuss actionable insights for practitioners.